Pengembangan Kewirausahaan Perancangan Busana Pengantin Berbasis Teknologi E-Commerce Pada Lyniza Wedding - Sofyan Azis; Anita Febrianti Ayu Ashari; Hanifah Putri Handayani; Gita Safira Kurnia Dewi; Eni Heni Hermaliani; Sri Rahayu (Universitas Bina Sarana Informatika Kota Sukabumi, 2021)
Ease of accessing the internet is a very important factor in developing a business. In the current era of globalization, the E-Commerce website has become a successful alternative for business activists to support marketing in the internet world. The wedding dress design is a very popular business which is important for people who want to get married without using rental services. This is useful for wedding dress rental service entrepreneurs who want to market wedding dresses to their customers. This study aims to fulfill the availability of a promotional system that can make it easier for prospective customers to manage product information and tailoring services or wedding dress designs, make it easier for prospective customers to place orders, and make reports more efficient. The research method used is descriptive analysis through data collection by conducting observations and interviews to analyze business plans, implementation methods, and business development. Meanwhile, the system developed for the website implementation design uses an object-based approach and the PHP MySQL platform. Thus, the application of e-Commerce that will be developed in the Lyniza Wedding Boutique business can handle the trade process which consists of the process of obtaining information in the form of a bridal fashion catalog as a promotional tool and can place orders as stated on the website catalog or design customization according to the wishes of potential customers, and facilitate employees and owners in compiling reports.Keywords: Entrepreneur, E-commerce, Wedding Dress